Ensuring transparency and integrity in public decision making and electoral processes in the State of Mexico - Prats, Mariana (OECD Working Papers on Public Governance, 2022)
This paper provides recommendations to foster integrity and transparency in decision making in the State of Mexico, by regulating access and promoting stakeholder engagement; and to enhance transparency and integrity in the funding of political parties and election campaigns. It addresses current challenges related to political finance such as cash contributions and clientelism, as well as the need to ensure adequate audit capacities and effective sanctions that advance accountability. Likewise, it analyses the state of play in terms of interactions between stakeholders, on the one hand, and public officials and legislators, on the other, providing recommendations to prevent policy capture, preserve integrity, and strengthen transparency